2018
DOI: 10.1007/jhep10(2018)075
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature enhancement of semi-annihilation and the AMS-02 positron anomaly

Abstract: Semi-annihilation is a generic feature of particle dark matter that is most easily probed by cosmic ray experiments. We explore models where the semi-annihilation cross section is enhanced at late times and low temperatures by the presence of an s-channel resonance near threshold. The relic density is then sensitive to the evolution of the dark matter temperature, and we compute expressions for the associated Boltzmann equation valid in general semi-annihilating models. At late times, a self-heating effect war… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Similar behaviour of DM also occurs in a more complicated DM model based on D 3 symmetry [54]. Indirect detection of Z 3 DM was considered in [55,56]. Further developments in connection with radiative neutrino mass were studied in [57][58][59].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Similar behaviour of DM also occurs in a more complicated DM model based on D 3 symmetry [54]. Indirect detection of Z 3 DM was considered in [55,56]. Further developments in connection with radiative neutrino mass were studied in [57][58][59].…”
Section: Introductionmentioning
confidence: 82%
“…The collision term C[f ] contains contributions from all possible interactions including elastic scattering, annihilation and semi-annihilation. The explicit expressions for the collision term and its moments can be found in [76] and for the contribution of semi-annihilation in the appendix A of [56]. 3 This system of cBE has been then used to find the improved relic density for the points situated on the boundary of the parameter space set by the absolute stability bound, i.e.…”
Section: Relic Densitymentioning
confidence: 99%
“…Semi-annihilations are present in a number of realistic models (see e.g. [10][11][12][13]) and not only are they subject to weakened direct detection limits, but also lead to peculiar phenomenology concerning the indirect detection [14] and the core-cusp cosmological problem [15][16][17].…”
Section: Jhep06(2021)026mentioning
confidence: 99%
“…This has been done recently in the context of DM freeze-out in [31,32], where it has been also shown that solving the system of equations for coupled 0-th and 2-nd moment (cBE) of (4.1) instead often gives from fairly to very good estimate of the resulting relic density. 4 At the same time the structure of the semi-annihilation and semi-production rates is technically more challenging due to the necessity of performing thermal averages on pairs of particles with different temperatures [14,15,33]. Having all this in mind we therefore leave full numerical solution of (4.1) to future work, while here we focus on the system of cBE.…”
Section: Boltzmann Equationsmentioning
confidence: 99%
“…[24]. Indirect detection of Z 3 DM was considered in [25,26]. The cubic coupling can contribute to 3 → 2 scattering for Z 3 strongly interacting (SIMP) DM [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%